Influence of fibre surface treatments and textile process on the properties of natural composites - Nag, Ranajit Kumar (2015)
The objective of this work is to understand the influence of fibre surface treatment as well as yarn twist on the tensile properties of unidirectional (UD) jute polyester composites. Jute and polyester are chosen in this work as both are cheap. As received jute yarn, physical and chemical surface treated jute yarn and raw jute fibre are used to manufacture UD composites. Physical surface treatment includes removing yarn hairs, sizing by hydroxyethyl cellulose (HEC), water treatment, sizing by cellulose nano-particle (CNP) and chemical treatment includes mercerisation with and without applying tension. Composites manufactured with unsized hairy yarn show an increase in tensile modulus and a decrease in strain at failure compared to composites manufactured with unsized hairless yarn in the longitudinal direction. However yarn hairs do not affect the tensile strength of composites. Application of HEC improves the tensile properties of composites with respect to composites manufactured with unsized yarn. Water treatment of yarn with tension enhances the tensile properties of composites and water treatment of yarn without tension decreases the tensile properties of composite with respect to composites manufactured with untreated yarn. Similar to water treatment, composites manufactured with alkali treated yarn with tension show higher tensile strength with respect to composites manufactured with alkali treated yarn without tension. Non-dried CNP treatment of yarn improves the tensile properties of composites. Composites manufactured with raw fibres have increased tensile properties with respect to composites manufactured with twisted yarn.